Vulvo-vaginal-gingival syndrome – a case report - Adamczyk, Michał; Młynarski, Tomasz; Sierocińska-Sawa, Jadwiga; Bednarek, Wiesława; Kwaśniewski, Wojciech; Chodorowska, Grażyna; Krasowska, Dorota (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction . Vulvo-vaginal-gingival syndrome is a rare variant of lichen planus. The disease affects mucous membranes of the oral cavity and genitals. It usually affects middle-aged females and most frequently presents as painful erosions. First-line treatment includes topical and systemic corticosteroids. If untreated, the disease may result in mucocutaneous scarring and stricture formation in affected organs. Therefore early diagnosis and appropriate treatment is essential. Objective . To present a patient with vulvo-vaginal-gingival syndrome treated with methylprednisolone, cyclosporin and tacrolimus ointment. Case report . A 54-year-old female patient with a several-year history of oral and genital complaints, formerly treated for periodontosis and candidiasis, was admitted to the Department of Dermatology in Lublin, where on the basis of clinical features and laboratory findings a diagnosis of vulvo-vaginal-gingival syndrome was established. The treatment included intravenous steroid pulse, cyclosporin A and 0.1% tacrolimus ointment and resulted in healing of erosions and regression of symptoms. Conclusions . A multidisciplinary approach is necessary in the treatment and management of vulvo-vaginal-gingival syndrome. The disease should be taken into consideration in differential diagnosis of chronic inflammations affecting the oral cavity and genital mucous membranes, with erosions dominating in the clinical picture.